Outcomes of STN-DBS in PD Patients With Different Rates of Disease Progression Over One Year of Follow-Up - Qi, Renli; Geng, Xin; Huang, Baihui; Chen, Ye; Jiang, Honggao; Zou, Yanghong; Wang, Wei; Li, Yubin; Li, Yushan; Yin, Lei; Liu, Anxiong; Yang, Xuelan; et al. (Frontiers in Neurology, 2020)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder, and the rate of progression is different across individuals. Subthalamic nucleus deep brain stimulation (STN-DBS) has been shown to produce long-term symptom improvement in PD. In this retrospective study, we wanted to explore the effects of bilateral STN-DBS in PD patients with different rates of disease progression. Forty patients with PD were included. An index of progression rate was calculated by the ratio of the Unified Parkinson Disease Rating Scale, part III (UPDRS-III) score in the off-medication condition at baseline and disease duration. The patients were divided into fast, medium and slow progression groups by this index. The outcome measurements at the 1st, 6th and 12th months after surgery were the changes in UPDRS-III scores in the off-medication/on-stimulation condition compared with the baseline. We found the following: 1. Motor functions in the different PD progression groups were improved by bilateral STN-DBS treatment at one-year follow-up. 2. However, compared to the slow and medium progression groups, the fast progression group had less improvement at the 6th and 12th month follow-up. The results indicated that bilateral STN-DBS can improve motor functions of Parkinson's patients over one year follow-up. Moreover, the outcomes in the slow and medium progression patients were better than those with fast progression rates.